Cases on corporate social responsibility and contemporary issues in organizations - Antonaras, Alexandros, 1972-; Dekoulou, Paraskevi, 1980- (Advances in business information systems and analytics (ABISA) book series., 2019)
"This book contains case studies elaborating on strategies and policies enacted by contemporary organizations to contribute to environmental and social issues, as well as to economic and financial ones. It also examines a number of organizations in different industry sectors, which effectively make decisions, design and enact CSR and sustainability strategies"--